Representation of Europe in Geography Textbooks of the 7th to 9th Grade - Zecha, Stefanie (Journal of Geography Education, 2006)
From the point of view of geography education, Europe has been an important theme for a long time. Meanwhile, every geography textbook refers to Europe and the European Union. The intention is that the students can judge their own opinion and that they develop a Europe consciousness of their own. This is especially achieved by curricula and textbooks, which usually are focused by school work. It is the target of this study to understand the character of the European dimension in actual Portuguese geography textbooks of the 7th to 9th grade. A treatment of quantitative and qualitative methods was developed, which corresponds to the demands of the matter and is suited to achieve a thorough understanding by its straightness and great comprehensibility. By means of quantitative analysis, the study examines how often each European area is mentioned, how many illustrations contain an European dimension and how strong the particular thematic points of the category systems Europe in general and European Union are stressed. The results are consolidated in qualitative analysis.